Pemikiran Ekonomi Islam Pada Masa Imam Al Ghazali (405-505H) - Utami, Rizky Ananda; Arif, Muhammad (Journal of Student Development Informatics Management (JoSDIM), 2024)
The extensive and profound thoughts of Imam Al-Ghazali in the realms of Islamic spirituality and philosophy have enriched the understanding of various facets of life, including economic principles. This research aims to explore the foundations of Islamic economic thought according to Imam Al-Ghazali in his monumental works. The study focuses on analyzing economic concepts reflected in Al-Ghazali's works, such as "Ihya Ulumuddin" and "Al-Mustasfa." The analytical method employed involves a qualitative approach, conducting an in-depth examination of Al-Ghazali's classical texts relevant to economics, emphasizing aspects of justice, business ethics, zakat, and perspectives on greed in an economic context. The research methodology utilizes a literature review approach, where information is gathered from books and writings by the respective researcher. The findings highlight Al-Ghazali's contributions to Islamic economic thought, emphasizing the importance of justice, transparency, and ethics in economic activities. The implications of Al-Ghazali's thoughts in shaping a fair, responsible, and blessed economic foundation take center stage in this study. These findings contribute to a deeper understanding of Islamic economic principles and the values advocated by this eminent figure within the economic context of his time.